Adding α-pinene as a novel application for sulfur dioxide-free in red wine. Issue 1 (1st January 2020) - Hou, Chih-Yao; Hou, Zheng-Ting; Lin, Chia-Min; Shih, Ming-Kuei; Chen, Yu-Wei; Lai, Yu-Heng
ABSTRACT: Sulfur dioxide (SO2 ) is an efficient additive that is used during winemaking to prevent microbial contamination as well as the oxidation and color changes caused by enzymatic and nonenzymatic reactions. However, this compound can cause allergic reactions to humans. In this study, α-pinene, a monomeric compound derived from fruits, was used to be an alternative for sulfur dioxide in red wine fermentation. Three concentrations of α-pinene, 0.125%, 0.25%, or 0.5%, were used. The red wine without additive or SO2 was used as controls. No significant differences were found in total soluble solids, pH values, titratable acidity, and ethanol content (n = 3, p < .05) though lower ethanol content was observed in the group at 0.5% α-pinene. The antibacterial results were the same between adding α-pinene and SO2 . In the α-pinene group, significantly higher L and a values as well as transmittance were obtained than in the control and SO2 groups. Higher free radical scavenging ability was also obtained in the groups of α-pinene. However, the group with the highest concentration, 0.5%, showed negative effects to ethanol production and sensory performance. Better physicochemical and sensory characteristics were obtained in the groups at 0.125% or 0.25% of α-pinene, particularly, when 0.125% of α-pinene was added. Thus, α-pinene at 0.125% should be the optimal concentration for a potential alternative for SO2 in winemaking.